An obituary for austerity narratives? An experimental analysis of public opinion shifts and class dynamics during the Covid-19 crisis - Emanuele Ferragina; Andrew Zola (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2020)
The Covid-19 pandemic is disrupting the international political economy context unlike any event since World War II. As a consequence, the French government has, at least momentarily, reversed decades of fiscal consolidation policies sedimented around austerity narratives by instating a costly emergency furlough scheme for a third of the workforce. This crisis provides a natural setting to investigate the relations among an emerging "critical juncture" in political economy, public preferences, and the salience of austerity narratives. We collected panel data and administered two experiments to test if citizens' viewpoints are sensitive to the trade-off between health and economics, still receptive to austerity narratives, and conditioned by socioeconomic status in supporting them. We find public viewpoints were highly swayable between health and economic concerns at the first peak of the epidemic outbreak in April 2020, but they were not influenced by the austerity narratives during the phase-out of the lockdown in June, with the exception of the upper class. Overall, public support is shifting in favor of increased social spending, and austerity might no longer inhabit the majority's "common sense." We conclude with further implications for the study of class and conflict in a post-pandemic world.
Keywords: 330; austerity narratives; class dynamics; constructivism; Covid-19; crisis; public opinion; welfare state